Effects of laser processing parameters on solidification microstructures of ternary Al2O3/YAG/ZrO2 eutectic in situ composite and its thermal property - 苏海军 张军 刘林 傅恒志 (Transactions of Nonferrous Metals Society of China, 2009)
Rapid surface resolidification with a high powered CO2-laser was performed in preparing directionally solidified Al2O3/YAG/ZrO2 ternary eutectic ceramic in situ composite. The effects of laser processing parameters on the solidification microstructure characteristics and thermal properties were studied by scanning electron microscopy （SEM）, energy dispersive spectroscopy （EDS）, X-ray diffractometry （XRD） and synthetically thermal analysis （STA）. Detailed investigations of the influence of laser power and scanning rate on the preparation and microstructural parameters of the ternary eutectic were presented. Moreover, the eutectic phase separation rule at high temperature was discussed. The results indicate that solidification microstructure of the ternary eutectic composite is greatly influenced by the laser processing parameters. The synthetically thermal analysis shows that the eutectic temperature of ternary Al2O3/YAG/ZrO2 composite is 1 738 ℃, well matching the phase diagram of Al2O3-Y2O3-ZrO2.